2021
DOI: 10.1177/1352458521999651
|View full text |Cite
|
Sign up to set email alerts
|

Juxtacortical susceptibility changes in progressive multifocal leukoencephalopathy at the gray–white matter junction correlates with iron-enriched macrophages

Abstract: Objective: Describe magnetic resonance imaging (MRI) susceptibility changes in progressive multifocal leukoencephalopathy (PML) and identify neuropathological correlates. Methods: PML cases and matched controls with primary central nervous system lymphoma (PCNSL) were retrospectively identified. MRI brain at 3 T and 7 T were reviewed. MRI-pathology correlations in fixed brain autopsy tissue were conducted in three subjects with confirmed PML. Results: With PML ( n = 26 total, n = 5 multiple sclerosis natalizum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
(28 reference statements)
1
9
0
Order By: Relevance
“…Hemorrhage, iron accumulation, and calcification are depicted in diverse tissues using GRE sequences with T2*-based contrast [ 12 ]. A recent study matched the observed changes with neuropathological findings and suggested that susceptibility changes are correlated with iron accumulation in macrophages [ 13 ]. Additionally, similar findings have been reported in progressive multifocal leukoencephalopathy and multiple sclerosis, suggesting blood–brain barrier dysfunction, decreased iron clearance owing to axonal dysfunction, and dysregulation of iron transport proteins as causes of iron deposition [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 62%
“…Hemorrhage, iron accumulation, and calcification are depicted in diverse tissues using GRE sequences with T2*-based contrast [ 12 ]. A recent study matched the observed changes with neuropathological findings and suggested that susceptibility changes are correlated with iron accumulation in macrophages [ 13 ]. Additionally, similar findings have been reported in progressive multifocal leukoencephalopathy and multiple sclerosis, suggesting blood–brain barrier dysfunction, decreased iron clearance owing to axonal dysfunction, and dysregulation of iron transport proteins as causes of iron deposition [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 62%
“…[3][4][5][6][7]9 Mahajan et al (2021) reported that juxtacortical lesions on MRI correlate with iron-enriched macrophages based on three autopsy cases in which PML developed after treatment with natalizumab for multiple sclerosis. 10 First, the background of PML is different. Second, they used diaminobenzidine-enhanced Turnbull staining to detect both ferric and ferrous non-heme iron as well as immunohistochemistry for the ferritin-light chain.…”
Section: Discussionmentioning
confidence: 99%
“…Mahajan et al (2021) reported that in three patients who developed PML after treatment with natalizumab for multiple sclerosis, susceptibility changes in MRI correlated with pathological accumulation of iron in macrophages. 10 Herein, we report a case of PML with massive hypointense changes in juxtacortical lesions in a 71-year-old woman who had been treated with rituximab-containing chemotherapy for follicular lymphoma for 16 months. Neuropathological examination revealed iron deposits with hemosiderin-phagocytic macrophages in the U-fibers of the occipital lobes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations